THE PEMBERIAN INTERVENSI SLOW STROKE BACK MASSAGE MENURUNKAN TEKANAN DARAH PADA WANITA MIDDLE AGE DENGAN KONDISI PRE-HYPERTENSION DI BANJAR BATAN BUAH, DESA KESIMAN, KECAMATAN DENPASAR TIMUR, BALI - A.A Arista Shinta; I Made Niko Winaya; Ni Wayan Tianing (Majalah Ilmiah Fisioterapi Indonesia, 2015)
The aim of this study is to know the effect of this intervention to decrease blood pressure in middle age women with pre-hypertension at Banjar Batan Buah, Kesiman Village, East Denpasar Sub-District, Bali. The method of this study is pre-eksperimental with one group design pre test – post test design. This study used 21 samples which were taken by Purposive sampling technique. And then they were treated with slow stroke back massage, and the data was collected with sphygmomanometer and used Saphiro Wilk Test as normality test. The result is p<0.05 which mean it’s not distributed normally. This study used Wilcoxon Signed Rank Test to analyze the impact of slow stroke back massage. This study used spps 16.0 version and showed that sistole and diastole of the blood pressure decreased significantly (p<0,05). In conclusion, there was a significant effect of slow stroke back massage to the decrease of the blood pressureof sistole 9,09% and diastole 10,42% in middle-age women with pre-hypertension.